Analytical models of decision-making in state cybersecurity systems under conditions of uncertainty - Чепурна, Олена Євгенівна; Чепурна, О. Є.; Chepurna, Olena Ye. (Одеса : Фенікс, 2026)
The functioning of state-level cybersecurity systems takes place in conditions of uncertainty, which is both objective and informational. On the one hand, cyber threats are formed as random processes with significant variability of parameters, which makes it impossible to accurately predict them. On the other hand, the available data on potential attacks, their probability and the scale of consequences are fragmented, incomplete and often contradictory, which limits the possibilities of their direct use in formalized decisionmaking procedures. Under such conditions, the cybersecurity management process acquires the features of a task with incomplete information, where not only the of threat parameters, but also the degree of trust in these assessments plays a significant role.
Chepurna O. Analytical models of decision-making in state cybersecurity systems under conditions of uncertainty. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / за заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 515-518. URL: https://doi.org/10.32837/11300.33292